Vertical integration and operational flexibility - Michele Moretto; Gianpaolo Rossini (Fondazione Eni Enrico Mattei (FEEM), 2008)
The main aim of the paper is to highlight the relation between flexibility and vertical integration. To this purpose, we go through the selection of the optimal degree of vertical disintegration of a flexible firm which operates in a dynamic uncertain environment. The enterprise we model enjoys flexibility since it can switch from a certain amount of disintegration to vertical integration and viceversa. This means that the firm never loses vertical control, i.e., the ability to produce all inputs even when it buys them in the market. This sort of flexibility makes for results which are somehow contrary to the Industrial Organization recent literature and closer to the Operations Research results. In this sense we provide a bridge between the two approaches and rescue Industrial Organization from counterintuitive conclusions.
Keywords: L24; G31; C61; 330; Vertical Integration; Outsourcing; Entry; Flexibility; Vertikale Konzentration; Produktionsplanung; Flexibilität; Outsourcing; Unternehmensorganisation; Operations Research; Theorie